ANALISIS STRATEGI MANAJEMEN SMK DI SUKOHARJO SEBAGAI UPAYA PENGEMBANGANSDM PENGAJAR - sulistyadi, kohar (TALENTA, 2014)
School education is education that is obtained starting from kindergarten to university by a person in uniform , and systematic. Sudrajat (2008 ) describes the concept of school management as a process of school activities for the benefit of students , so that all the components including the utilization of all human resources directed schools to achieve effective management of the school . Sukoharjo government issued free school policy that began on January 2, 2007 is expected to encourage increased public intellectual and fulfill the right to education and to realize the nine-year compulsory education program . To be able to develop the analysis it is necessary to study the effect of free school policy as a management strategy inthe development of vocational schools in Sukoharjo in order to create the hyuman resources Excellence